Safety, short-term patient-reported outcomes, and cosmetic satisfaction of gasless transaxillary endoscopic thyroidectomy: a retrospective analysis of 530 patients - Yifan He; Jie Yuan; Xiyu He; Yawen Bai; Zesheng Zeng; Jianfeng Sheng (Frontiers in Endocrinology, 2026)
Background Gasless transaxillary endoscopic thyroidectomy (GTET) eliminates visible cervical scarring and has been increasingly adopted for managing unilateral thyroid diseases. This study aimed to evaluate its safety, feasibility, perioperative complications, procedure-specific discomfort, and cosmetic satisfaction. Methods We retrospectively reviewed 530 consecutive patients with unilateral thyroid disease who underwent GTET between January 2023 and February 2026. To evaluate surgical experience, 406 patients with papillary thyroid carcinoma (PTC) were chronologically divided into early- and late-phase groups (203 cases each). Multivariable linear regression adjusted for baseline confounders. Serum PTH and calcium were measured at 36 hours. Chest wall sensory disturbance and sternocleidomastoid (SCM) discomfort were evaluated at 1 week and 3 months using a modified Verbal Rating Scale (VRS, 0–3), and cosmetic satisfaction via Patient Satisfaction Score (PSS, 0–3). Results Among 530 patients (406 PTC, 124 benign), four (0.75%) required conversion to open surgery (two for internal jugular vein bleeding, two for intraoperative recurrent laryngeal nerve transection with immediate neurorrhaphy; none developed permanent paralysis). Postoperative hematoma occurred in six patients (1.13%; one reoperated, five managed conservatively). Two tracheal and one esophageal injury were repaired endoscopically, all recovering within 2 months. Transient vocal cord paralysis occurred in 34 patients (6.42%), permanent in three (0.57%), and transient hypoparathyroidism in 11 (2.08%). Multivariable regression confirmed the late phase independently predicted shorter operative time (β = -14.2 min, P < 0.001) and higher postoperative PTH (β = 4.8 pg/mL, P < 0.001). Chest wall disturbance and SCM discomfort improved significantly from 1 week to 3 months (VRS: 1.41 ± 0.53 vs. 0.36 ± 0.42 and 1.84 ± 0.55 vs. 0.43 ± 0.53, P < 0.001). Over a median follow-up of 25.3 months (IQR: 9.2–34.6), no primary site recurrences occurred. Six patients (1.13%) developed metachronous micro-PTC (0.1–0.4 cm) in the contralateral lobe, successfully treated with completion thyroidectomy. Conclusions GTET is a safe and feasible option for carefully selected patients with unilateral thyroid disease, offering favorable cosmetic satisfaction and acceptable morbidity. Procedure-related symptoms are transient. Accumulating surgical experience independently improves operational efficiency and parathyroid preservation.